Combustion characteristic of premixed H2/air in the micro cavity combustor with guide vanes. (15th January 2022) - Gao, Wei; Yan, Yunfei; Shen, Kaiming; Huang, Lujing; Zhao, Ting; Gao, Bo
Abstract: Micro-scale combustion is facing the problems of ignition difficulty, combustion instability, and low combustion efficiency. Therefore, it is necessary to improve the combustion characteristics in micro-combustor to expand the application range of micro-combustor. Based on the traditional cavity combustor (TCC), a cavity combustor with guide vanes (CCGV) was constructed to further strengthen the effect of the cavity. The combustion characteristics of TCC and CCGV at different inlet velocities and equivalence ratios were compared and analyzed. And the combustion characteristics of CCGV were researched under different guide vane geometries. The temperature and the area of high-temperature zones in the cavity of CCGV are significantly higher and bigger than the TCC respectively. The cavity of CCGV has a better preheating and ignition effect than TCC. When the inlet velocity is 8 m/s, the maximum temperature in cavities of CCGV is 326 K higher than TCC. When the equivalence ratio increases from 0.6 to 1.2, the blow-off limits of TCC and CCGV increase from 3 m/s and 33 m/s to 14 m/s and 121.5 m/s, respectively. The CCGV with S/L 3  = 0.12/0.4 and α  = 45° has a better practical application value. When the inlet velocity is 14 m/s, compared with S/L 3  = 0.12/0.4, the combustion efficiency of S/L 3  = 0.15/0.5, S/L 3  = 0.18/0.6 and S/L 3  = 0.21/0.7 increases by 1.21 %, 2.25 % and 2.61 %, respectively, while the pressure loss increases by 3.79 %, 5.70 % and 13.68 %, respectively. When the inlet velocity increases are 20 m/s, the combustion efficiency and is 74.46 %, 87.97 %, and 87.51 %, respectively. The pressure loss of α  = 60° is 4.35 % higher than that of α  = 45°. Highlights: The combustion characteristics of TCC and CCGV were compared and analyzed. The cavity of CCGV has a better preheating and ignition effect than TCC. The CCGV has higher blow-off limit and combustion efficiency than TCC. The CCGV with S/L 3  = 0.12/0.4 and α  = 45° has a better practical application value.